Nilai-Nilai Moderasi Beragama Pada Mahasiswa Di Sekolah Tinggi Agama Islam Rasyidiyah Khalidiyah Amuntai Kalimantan Selatan - Ria Susanti Ria; Rosa Bella Napitupulu (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2023)
Religious moderation education does not only specify how to behave when different religions, but also focuses on how to behave with the same religion. Therefore this study aims to explore the understanding of Students in Rasyidiyah Khalidiyah Amuntai Islamic High School (STAI) South Kalimantan on the basic concepts, principles, and character values of religious moderation through analysis of Islamic Religious Education Materials and through interviews. The research method used is descriptive qualitative, the research subjects were STAI Rakha Amuntai students. Research result; that STAI Rakha Amuntai students' understanding of basic concepts, principles and character values of religious moderation has been illustrated through their process of analyzing Islamic Religious Education Materials and through interviews. However, the fact is that in their daily lives there is still behavior that goes beyond the principles and values of religious moderation, as can be seen in their circle of friends, this means that they not yet have the principles of equality or musawah. And the results of the analysis of the Islamic Religious Education Materials (PAI), the students agreed that the PAI Material contains the character value of religious moderation, because the basis of PAI material is the Al-Qur'an, which in it calls for a fair attitude (QS. Annisa: 58), balance (QS. Al-Hajj: 60), and tolerance (QS. Al-Baqarah: 256).